COMBINING MASTERMIND QUESTION AND QUICK INTELLIGENT QUIZ TO IMPROVE THE CONTENT SPEAKING ABILITY OF THE SENIOR HIGH SCHOOL STUDENTS - Febrina Febrina; Aryuliva Adnan (Universitas Negeri Padang, 2013)
Abstract The purposes of this paper were to (1) describe the most problem faced by students in learning speaking (2) explain the combination of mastermind question and quick intelligent quiz to solve the most problem faced by students (3) implement the combination of mastermind question and quick intelligent quiz in teaching speaking at school. The most problem faced by students in this paper is the lack of students’ content in speaking. The way to solve this problem can be done by implementing mastermind question and quick intelligent quiz. Through giving a question from mastermind question and implementing it in quick intelligent quiz, it can improve students’ critical thinking then develop students’ content in speaking. Key word : Speaking, Mastermind Question, Quick Intelligent Quiz, Critical Thinking, Content.